# What is the derivative of #f(t) = (2t-3te^t, 2t^2+3t ) #?

God bless...I hope the explanation is useful.

By signing up, you agree to our Terms of Service and Privacy Policy

The derivative of ( f(t) = (2t - 3te^t, 2t^2 + 3t) ) with respect to ( t ) is:

[ f'(t) = \left(2 - (3 + 3t)e^t, 4t + 3\right) ]

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you find the equation of a line tangent to the curve at point #t=-1# given the parametric equations #x=t^3+2t# and #y=t^2+t+1#?
- How do you differentiate the following parametric equation: # x(t)=lnt-2t, y(t)= cos^2t #?
- What is the derivative of #f(t) = (t^3-te^(1-t) , t^2-6t+e^t ) #?
- How do you differentiate the following parametric equation: # x(t)=te^t-lnt, y(t)= t^3e^t-t^2+t#?
- How do you find d/dt given #y=t^3 - 3t# and #x=t^2#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7